Is iron deficiency related with increased body weight? A cross-sectional study - Kaner, Gülşah; Pekcan, Gülden; Pamuk, Gülseren; Pamuk, Barış Önder; Amoutzopoulos, Birdem (Progress in Nutrition, 2016)
Aim: To investigate the relationship between iron deficiency and obesity through dietary intake and inflammation parameters in overweight and obese women. Material/Methods: A total of 619 women, aged 20-49 years with normal weight (n=170), overweight (n=179), and obesity (n=270) were involved in the study. The biochemical parameters [whole blood count (WBC), anaemia parameters, C-reactive protein (CRP), high sensitive C-reactive protein (hsCRP), soluble transferrin receptor (sTfR)] and bioelectrical impedance analysis were analysed one at the beginning of study. Results:  Although dietary iron intake were higher in the overweight and obese groups, their WBC, CRP, hsCRP and sTfR levels were lower than women with normal weight (p